PERSEPSI PETANI BALI TERHADAP KUT YANG DISEMPURNAKAN - OKA SUARDI, I D. P. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 0, No. 1 November 2000, 2012)
There are many problems on farm credit distribution, such as: absorption level is low, credit arrears, and undicipline of personels. In anticipation, the scheme of the credit has been revised, to involve: credit interest, credit plafonds, bank as a channeling agent, village cooperative unit as an executing agent, and the participation of NGOs. The aim of this research was to identify the perception of farmers about the farm credit that has been revised. Porposive sampling method was used to determine the location and samples. Survey method was employed in the data collection, and data analysis used description method. The perception of the farmers was that: credit conditions are accepted, the credit interest is low, plafonds of the credit is enough to cost the farming, and credit realization is late. Based on these results, it is suggested that the credit personels increase their performance so that credit distribution will be successful.
Keywords: Farm Credit, Farm Credi, Revised, Perception